Assessment Of Lercanidipine Hydrochloride For Transdermal Delivery: Physicochemical, In-Vitro And Ex-Vivo Characterization Of Matrix Type Lercanidipine Hydrochloride Transdermal Patches - SUBHASH P.G.,; DINESH B.M.,; RAVIKUMAR M., (International Journal of Pharma and Bio Sciences, 2012)
This article reports the assessment of lercanidipine hydrochloride (LH) for transdermal delivery. In-vitro permeation studies were carried out across the porcine ear skin in presence of various penetration enhancers. Pharmaceutical excipients and chemicals namely tween-60, dimethyl formamide (DMF), sodium tauro glycolate (STG), cinnamaldehyde, menthol and hyaluronidase were facilitated to evaluate as effective penetration enhancer. Among all, hyaluronidase emerged as effective penetration enhancer with highest flux 111.8±0.030 µg/cm2/hr, Kp 0.0172±0.040 cm/hr and enhancement ratio 5.37±0.01 than others. Later, EL1, EL2, EL3, EL4, EL5 and EL6 LH transdermal patches were prepared by incorporating EC and PVP K-30 as polymers in 3:2, 2:3, 2:1, 1:2, 4:1, and 1:4 ratios respectively. All, six transdermal patches loaded with 10 mg of LH/3.14 cm2 area of patch, optimized hyaluronidase (5% w/w) as penetration enhancer, n - dibutyl phthalate (30% w/w) as a plasticizer. Transdermal patches revealed satisfactory physicochemical properties. Among six formulations, EL4 exhibited highest cumulative percent of drug permeation (84.84±1.64%), transdermal flux (114.4±3.21µg/cm2/hr), permeability coefficient (1.14×10-2±1.99 cm/hr) and diffusion coefficient (8.468×10-8±0.086 cm/hr). The curve fitment data indicated that the in-vitro permeation data of model formulations fitted well into zero order equation (average R2=0.9713 to 0.9866) better than first order and Higuchi model. The stability studies revealed that no morphological changes in patches were found insignificant variation in drug content. Furthermore, the satisfactory results were supported by one way ANOVA.